2018
DOI: 10.1002/smtd.201800108
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Graphene‐Based Materials and Water Molecules toward Actuator and Electricity‐Generator Applications

Abstract: of chemical energy to electric and/or mechanical energy, which is potentially profitable for various applications such as sensors, actuators, robots, switches, artificial muscles, and electricity generators. [22, Benefiting from the large available surface area, the unique electrical, thermal, and mechanical properties of graphene and/or its derivatives, as well as the ease of structure functionalization, device-oriented applications based on the interactions between graphene materials and water molecules have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…Artificial actuators are stimuli-sensitive devices that can undergo a reversible change in shape, volume, modulus, or some other mechanical properties in response to various external stimuli, which have attracted tremendous attentions attribute to the wide applications for robots, intelligent switch, smart sensors, memory chips, and prosthetic devices (Kim and Lieber, 1999;Jang et al, 2008;Huang et al, 2012;Xue et al, 2015;Xu et al, 2018b). Usually, the external stimuli can be electrical, optical, thermal, humid, and other forms of stimulation depending on the actuation mechanism (Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial actuators are stimuli-sensitive devices that can undergo a reversible change in shape, volume, modulus, or some other mechanical properties in response to various external stimuli, which have attracted tremendous attentions attribute to the wide applications for robots, intelligent switch, smart sensors, memory chips, and prosthetic devices (Kim and Lieber, 1999;Jang et al, 2008;Huang et al, 2012;Xue et al, 2015;Xu et al, 2018b). Usually, the external stimuli can be electrical, optical, thermal, humid, and other forms of stimulation depending on the actuation mechanism (Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, as another carbon nanomaterial with just one atom layer thick, that features high electron conductivity, excellent mechanical flexibility, huge surface area, superior thermal conductivity and stability, has captured a broad research interest for using as material or structural component in the actuator fabrication (Novoselov et al, 2004;Zan et al, 2011;Cheng et al, 2016;Xu et al, 2018b;Liu Y. Q. et al, 2019). It could be not only served as the electrode in the electrically/electrochemically driven actuators, but also the energy converting component or active actuation component in the photothermal systems, as well as in the moisture actuators (Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that the hydration and/or dehydration of graphene-based materials could trigger the deformation of graphene sheets [8], which is potentially profitable for enzyme immobilization. Based on these concepts, we present an electrochemical enzyme sensor based on a 3D porous graphene coated hollow graphene fiber (PHGF) via a simple and effective shrink-effect-enabled enzyme immobilization method.…”
mentioning
confidence: 99%
“…After drying, chemically reduced graphene oxide (RGO) aggregated along the Cu wire (RGO/Cu, Fig. 1b) due to the spontaneous redox reaction between GO and Cu [8]. The etching of Cu wire in a mixture of FeCl 3 and HCl aqueous solution resulted in the formation of hollow graphene fiber (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation